Probiotic properties of Lactobacillus plantarum and application in prebiotic gummies. (15th January 2023) - Feng, Shucen; Wang, Haitao; Lin, Xinping; Liang, Huipeng; Zhang, Sufang; Chen, Yingxi; Ji, Chaofan
Abstract: The increasing demand for healthy food has led to a broad interest in developing new food products containing probiotics in recent years. In this study, the potential of probiotics and prebiotics was assessed to develop novel gummies. The results showed probiotic properties in twenty-five Lactobacillus plantarum ( L. plantarum ) strains derived from fermented foods, confirming them to be safe for consumers, which can tolerate the simulated gastrointestinal fluids (SGIF) to a certain extent. Additionally, the DPPH free radical ranging between 13.67 ± 0.35 to 15.98 ± 0.28 mg AAE/L was expressed as ascorbic acid equivalent (AAE). Afterward, the results showed that six mushroom polysaccharides had a proliferative effect on most potential probiotics. Besides, they could further protect the survival of L. plantarum YC-5 in the SGIF. With the protection of prebiotics, the number of viable cells in SGIF exceeded 7 log CFU/mL. The genomic analysis demonstrated that 106 genes were involved in saccharide metabolism in L. plantarum YC-5 . Finally, probiotics and prebiotics were used as raw materials to prepare the gummies. The results indicated that the gummies protected the probiotic L. plantarum YC-5 with little loss of activity in the SGIF. Therefore, preparing probiotics and prebiotics as gummies could be a promising probiotic food application. Highlights: Four strains of Lactobacillus plantarum screened for probiotic potential. Mushroom polysaccharides proliferated and protected against L. plantarum YC-5. Preparation probiotics and prebiotics as gummies.